Internal Flow Model of a Helical Centrifugal Atomizer for Cold Preservation Systems in the Fishing Industry - Raymundo, Carlos (2024)
Since 1960, a higher percentage of aquatic foods have been allocated for human consumption. In 2020, 89% of global fishery and aquaculture production was dedicated to this purpose. With the increasing demand in the industry, there has also been a development of quality and food safety standards. Therefore, the food preservation technique of refrigeration becomes essential to prevent input losses and maintain quality. This leads to the need for appropriate technology for the freezing process of aquatic foods on vessels. In this research, the study and consequently, the design of a swirl effect atomizer using tools based on mathematical models and complemented with numerical simulation (Ansys CFD: Computational Fluid Dynamics) is proposed. This cryogenic atomizer, in conjunction with another water atomizer, would produce ice in the form of tiny particles. This would increase the efficiency in the use of refrigeration resources by applying a layer of ice directly onto the food for freezing. Furthermore, by creating a portable design with fewer freezing elements requirements, space on the vessels would be optimized, allowing for greater food storage. Lastly, this research addresses the ability to generate freezing elements using the vortex chamber technique that combines cryogenic fluid and water. These elements do not affect the quality of aquatic foods.